Beyond a click: gratifications seeking from Facebook interaction / Zaridah Abdullah …(et al.] - Abdullah, Zaridah; Ibrahim, Mohd Nazri; Saaid, Shahnil Asmar; Din, Faizah; Abdul Rahman, Muhammad Fadhli (Faculty of Communication and Media Studies (FCMS), 2023)
The existence of social networking sites, especially Facebook, not only introduced a new method for the society to interact and socialize online, but it also provided a medium for the audiences to fulfil the needs of attaining information, sharing views and expressing emotions with virtual friends. Uses and gratifications theory explains that the audience will choose the medium that will gratify their needs. Previous studies on Facebook have mostly focused on youth, while studies pertaining to usage patterns among adult Facebook users still remain limited. Therefore, this study was conducted to identify adult users’ activities on Facebook and the gratifications they seek. A total of 310 adult Facebook users in the Klang Valley were selected for this study. The study found that the majority of adult Facebook users visit the site between 2-4 times a day, and most were done via smartphones. The activity that was mainly carried out on Facebook is to wish their friends on their birthdays or festive celebrations. In terms of media gratification, the majority of adult Facebook users utilise it to keep themselves up-to-date with long-lost friends’ development, following issues shared by virtual friends, and to give and receive moral support. Factor analysis that was done on media gratifications revealed 184Forum Komunikasi three distinct typologies: emotional needs, information needs and moral support needs. The study also found that there was no difference between men and women in terms of using the media to meet the requirements based on the two typologies concerned. The study concludes on the findings that similar to other users, adults also use Facebook in order to meet their various needs. In addition, this study has successfully introduced a new typology – moral support needs – where Facebook users seek wisdom or advice from religious experts, as well as virtual friends who can help in strengthening their morale.